Composição e distribuição florística em corredores ecológicos em regeneração natural - Magalhães, Júlio Henrique Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The interventions in the environment performed by humans in recent decades have changed the landscape and the natural ecosystems were reduced to fragments, which are now considered to be a shelter for the biodiversity that still exists. The present work behind the data obtained from a study conducted in four corridors located in the municipality of Paulista, SP, which connect different forest fragments amidst an eucalyptus matrix. These corridors are linear strips of land that were part of the eucalyptus plantation, where since 2002, a natural regeneration process is in course. We conducted a rapid ecological survey in the central corridors, and individuals exhibiting height ≥ 1.30 m were sampled in 268 plots of 20 x 25 m, covering an area of 13.4 ha. In total 11,111 individuals were recorded, distributed in 154 species, 100 genera and 47 families. Fabaceae and Myrtaceae were the richest families. The proximity of forest remnants affected the composition, density and richness of the natural regenerated areas. There was mostly greater similarity inside each corridor, and the observed variations in similarity were gradual among contiguous plots

As intervenções no meio ambiente exercidas pelo homem nas últimas décadas têm modificado a paisagem e reduzido os ecossistemas naturais a fragmentos, que são hoje, considerados reduto de grande parte da biodiversidade ainda existente. O presente trabalho trás os dados obtidos através de um estudo realizado em quatro corredores ecológicos localizados no Município de Lençóis Paulista, SP, que conectam diferentes fragmentos florestais em meio a uma matriz de eucalipto. Esses corredores ecológicos são faixas de terra lineares, que anteriormente faziam parte do plantio de eucalipto, aonde desde 2002, vem ocorrendo o processo de regeneração natural. Foi realizado um levantamento ecológico rápido na faixa central dos corredores amostrando os indivíduos vegetais com altura ≥ 1,30 m em 268 parcelas de 20 x 25 m, cobrindo uma área de 13,4 ha. No total foram amostrados 11.111 indivíduos, distribuídos em 154 espécies, 100 gêneros e 47 famílias. Fabaceae e Myrtaceae foram as famílias mais ricas. A proximidade com os fragmentos florestais afetou a composição, a densidade e a riqueza da regeneração natural. Houve tendência a uma variação gradual da similaridade florística ao longo de parcelas contíguas
Floristic composition and distribution of ecological corridors in natural regeneration
Keywords: Floresta - Reprodução; Florestas - Restauração; Eucalipto; Corredores (Ecologia); Ecologia vegetal